Morphological features of the heart of six mosquito species as revealed by scanning electron microscopy - Martins, Gustavo Ferreira; Ramalho- Ortigão, José Marcelo; Pimenta, Paulo Filemon Paolucci (International Journal of Tropical Insect Science, 2011)
The circulatory system in insects is formed by a dorsal vessel (heart) that is a tubular structure that pumps haemolymph in the insect body cavity. Up until now, much is known about the structural organization of the heart in certain Brachycera (Diptera) (e.g. Drosophila). In contrast, little information is available regarding members of the Nematocera suborder (e.g. mosquitoes), in spite of their relevance to human health. Considering their importance, details of the heart morphology of six mosquito species (Aedes albopictus, Ae. aegypti, Ae. fluviatilis, Culex quinquefasciatus, Anopheles darlingi and An. aquasalis) were investigated by scanning electron microscopy (SEM). The heart of the adult mosquitoes, both males and females, consists of a dorsal tubular structure in association with pericardial cells located alongside the heart and alary muscles displaying ramifications that extend from the body wall to the heart surface. The SEM analysis also revealed in detail the organization of the heart, including paired valves on the heart wall (ostia). This study provides a detailed analysis of the mosquito heart microanatomy and, in our view, represents a significant contribution towards the understanding of structural– functional relationships associated with the heart of mosquito.
Keywords: Heart; Pericardial cells; Alary muscles; Aedes albopictus; Aedes aegypti; Aedes fluviatilis; Culex quinquefasciatus; Anopheles darlingi; Anopheles aquasalis